Egg production feasibility in laying hen with access to grazing - Cruz Bermúdez, Ana; WingChing Jones, Rodolfo; Zamora Sanabria, Rebeca (Agronomía Mesoamericana, 2021)
Introduction. The production of hens with access to grazing integrates bird, fodder, and marketing management. Objective. To describe laying hens’ production systems with grazing access in Costa Rica and determine the feasibility of implementing aproduction model. Materials and methods. During the years 2017 and 2018, information on the production, health, grazing, and egg management was collected and analyzed in six farms with laying birds that have access to grazing. To determine the feasibility of the proposed production model, a cash flow (ten years) was prepared, which included the investments to develop the system, and an inflation rate of 10% through the years. The costs of investment, operation, and income from the sale of the eggs, discarded hens, and poultry litter were analyzed. The NPV, IRR, C/B ratio, and break-even point were calculated. Results. Sixty six percent of the systems use specialized birds, densities between 5 to 12, and 1 to 3 birds m-2 in the shed and grazing area, respectively. Grazing began at 22 and 32 weeks, with 2-10 h day-1. Five systems did not substitute feed for fodder; they consider it as an added value. The proposal is demanding in facilities, plot, and work equipment. Feeds represent 41% of the operational costs, followed by labor (22 %), and bird purchase (17 %). It is profitable, by obtaining a positive NPV ($31 455.39) and IRR of 21.48 % and the C/B ratio>1, and the investment will be recovered after six years. Conclusions. Farms with laying hens with access to grazing evaluated in this work could improve in nutritional aspects and forage cultivation. In addition, they are production systems that present economic indicators that favor their implementation.